A direct replication and extension of Popp and Serra (2016, experiment 1): better free recall and worse cued recall of animal names than object names, accounting for semantic similarity - Mah, Eric Y.; Grannon, Kelly E. L.; Campbell, Alison; Tamburri, Nicholas; Jamieson, Randall K.; Lindsay, D. Stephen (Frontiers in Psychology, 2023)
Introduction Free recall tends to be better for names of animate concepts such as animals than for names of inanimate objects. In Popp and Serra’s 2016 article, the authors replicated this “animacy effect” in free recall but when participants studied words in pairs (animate-animate pairs intermixed with inanimate-inanimate pairs) and were tested with cued recall, performance was better for inanimate-inanimate pairs than for animate-animate pairs (“reverse animacy”). We tested the replicability of this surprising effect and one possible explanation for the effect (semantic similarity). Methods Our Experiment 1 was a preregistered direct replication (N = 101) of Popp and Serra’s Experiment 1 (mixed-lists condition). In a second preregistered experiment conducted in four different samples (undergraduate N = 153, undergraduate N = 143, online Prolific N = 101, online Prolific/English-as-a-first-language N = 150), we manipulated the within-category semantic similarity of animal and object wordlists. Results AIn Experiment 1, just as in Popp and Serra, we observed an animacy effect for free recall and a reverse animacy effect for cued recall. Unlike Popp and Serra, we found that controlling for interference effects rendered the reverse animacy effect non-significant. We took this as evidence that characteristics of the stimulus sets (e.g., category structure, within-category similarity) may play a role in animacy and reverse animacy effects. In Experiment 2, in three out of our four samples, we observed reverse animacy effects when within-category similarity was higher for animals and when within-category similarity was equated for animals and objects. Discussion Our results suggest that the reverse animacy effect observed in Popp and Serra’s 2016 article is a robust and replicable effect, but that semantic similarity alone cannot explain the effect.